A case of heterotopic ovarian pregnancy after in vitro fertilization: early diagnosis and single-port access conservative laparoscopic treatment - Yeon Hee Hong; Hyojin Kim; Seul Ki Kim; Byung Chul Jee (Wolters Kluwer Medknow Publications, 2021)
Here, we reported the case of a 32-year-old pregnant woman who presented with sudden abdominal pain at 5 weeks of gestation and diagnosed as ruptured heterotopic ovarian pregnancy. She was conceived after in vitro fertilization. Right ovarian pregnancy was noticed, and we performed right ovarian wedge resection via single-port access laparoscopic surgery. Intrauterine pregnancy had remained intact, and she delivered a term baby. Rapid diagnosis in early gestation and minimally invasive laparoscopy resulted in a satisfactory pregnancy outcome without other complications. Single-port laparoscopic surgery can be feasible and appears to be a good first treatment option in a ruptured heterotopic ovarian pregnancy.